2010
DOI: 10.2174/1874920801003010010
|View full text |Cite
|
Sign up to set email alerts
|

Program and School Characteristics Related to Teacher Participation in School Health Promotion~!2009-07-07~!2009-12-13~!2010-03-09~!

Abstract: Abstract:The aim of this study was to investigate conditions related to teacher participation in the planning and implementation of the Norwegian part of the European Network of Health Promoting Schools. One hundred and four teachers responded to the questionnaire at baseline and at three year follow-up. Teachers' personal interest and regard for the program aim were the main predictors of their self-reported participation in the program. Conditions perceived as enabling or hindering program implementation, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Cooperation with other professions at the school is therefore necessary for successful health promotion in a broader sense in schools (Reuterswärd & Lagerström, 2010). Teachers' commitment to implementing health into their curriculum could be one way of increasing health promotion and getting pupils to understand the importance of health for their learning (Grieg Viig et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cooperation with other professions at the school is therefore necessary for successful health promotion in a broader sense in schools (Reuterswärd & Lagerström, 2010). Teachers' commitment to implementing health into their curriculum could be one way of increasing health promotion and getting pupils to understand the importance of health for their learning (Grieg Viig et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Three Austrian studies investigated capacity building in relation to provincial support strategies [ 33 ], perceived support by schools [ 32 ] and provision of a pilot training course [ 34 ] ( micro- and exosystem ) and two other studies examined a regional network through stakeholders perceptions of learning [ 35 ] and side effects of HP [ 36 ] ( micro- and mesosystem ). Five studies in Norway discussed participation of schools in the Norwegian network of HP in terms of program leader support [ 37 ], teacher motivation and participation [ 38 ] and school implementation [ 39 , 40 , 41 ] ( micro- and mesosystem ). In Scotland, HP is well integrated into the school system, with all schools being required (and being monitored) to become a HPS since 2007 ( macrosystem ).…”
Section: Resultsmentioning
confidence: 99%
“…The compatibility of HPS with the education system was discussed in many studies as being an important incentive for schools and some studies mentioned this occurring through new national curricula [ 39 , 40 , 42 ] and policies [ 66 ]. If alignment was not achieved, studies reported many undesirable ‘side-effects’ [ 36 ] with professed lack of time and the busy school workload being a common barrier reported when HP was not well integrated into the system [ 36 , 39 , 41 , 61 , 66 , 71 ]. Studies also reported on the different types of incentives that were provided to encourage school participation, including financial resources through grants and provision of time for health promotion work through substitute coverage [ 32 , 34 , 37 , 39 , 41 , 51 , 52 , 61 , 66 , 71 , 72 , 74 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, evaluation research from Norwegian health promoting schools indicates that the proposed relationship between health and educational outcomes motivated educational staff to adopt, implement and sustain the health promoting school Viig et al 2010 ). Similarly, evaluation research from Norwegian health promoting schools indicates that the proposed relationship between health and educational outcomes motivated educational staff to adopt, implement and sustain the health promoting school Viig et al 2010 ).…”
Section: The Health Promoting School: Effect Outcomes and Process Outmentioning
confidence: 99%